The Dialectics of Judicial Pardon as a Safety Valve in the Offense of Murder: A Substantive Justice Analysis under Law Number 1 of 2023 - Ramadinah, Tarisha Ersya; Rivanie, Syarif Saddam; Karim, Muhammad Said; Muhni, Afif (SIGn Journal of Social Science, 2025)
The fundamental transformation of national criminal law through the promulgation of the New Penal Code promotes a paradigm of substantive justice that triggers a normative dialectic regarding the existence of the formal legality principle of colonial legacy. This study aims to critically analyze the position of judicial pardon as an exceptional veiligheidsklep instrument to accommodate legal facts in specific murder offenses, while simultaneously assessing its effectiveness in maintaining the balance between legal certainty and human rights protection. The research method employed is normative legal research with statute, conceptual, and comparative approaches analyzed qualitatively using deductive logic and the legal dialectic method. The results indicate that the limitative restrictions of judicial pardon in Article 70 section (2) of the New Penal Code clash diametrically with the mandate of Article 53 section (2) of the Law, which obligates judges to prioritize substantive justice over formal legal certainty. These findings affirm that judicial pardon functions as a final filter post-operationalization of the primary filter, in the form of conventional grounds for excluding punishment, such as weer-exces and overmacht. Through the analysis of Decision Number 4/Pid.B/2024/PN Jnp, it is proven that exceptional judicial pardon in murder offenses with a low degree of culpability constitutes a judicial necessity to realize the objectives of restorative justice and the decolonization of national criminal law. The conclusion of this study emphasizes that judicial pardon is an instrument for salvaging human dignity and requires the support of accountable sentencing guidelines. Therefore, the Supreme Court is advised to immediately establish a Regulation regulating qualitative parameters for the application of pardon in grave offenses to avoid sentencing disparities and ensure the moral legitimacy of the law in the future Indonesian criminal justice system.